2021
DOI: 10.1177/20420188211030160
|View full text |Cite
|
Sign up to set email alerts
|

A case of adrenal Cushing’s syndrome and primary hyperparathyroidism due to an atypical parathyroid adenoma

Abstract: Cushing’s syndrome is a rare disorder of cortisol excess and is associated with significant morbidity and mortality. Hypercalcaemia due to hyperparathyroidism is a common condition; however, in 10% of young patients, it is associated with other endocrinopathies and occurs due to a genetic variant [e.g. multiple endocrine neoplasia (MEN) type 1 (MEN1), MEN2 or MEN4]. We report the case of a 31-year-old woman who was referred to the endocrinology out-patient service with an 8-month history of hirsutism, amenorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…However, still others reported an ATA in a young adolescent girl with poor respiratory reserve, where en bloc resection of the right parathyroid with right sided hemithyroidectomy was undertaken using local anaesthesia [2] . For both our cases, we conducted rapid intra-operative parathyroid hormone (PTH) during surgery that showed a sharp drop in PTH level that satisfied the Miami Criterion (>50 % PTH drop from either the greatest pre-incision or pre-excision PTH measurement in a blood sample 10 min after complete resection of a hyperfunctioning gland) for successful parathyroid gland resection, in line with others [9] . In addition, intraoperatively, we also undertook a frozen section which confirmed that the excised specimen is parathyroid gland for both cases.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…However, still others reported an ATA in a young adolescent girl with poor respiratory reserve, where en bloc resection of the right parathyroid with right sided hemithyroidectomy was undertaken using local anaesthesia [2] . For both our cases, we conducted rapid intra-operative parathyroid hormone (PTH) during surgery that showed a sharp drop in PTH level that satisfied the Miami Criterion (>50 % PTH drop from either the greatest pre-incision or pre-excision PTH measurement in a blood sample 10 min after complete resection of a hyperfunctioning gland) for successful parathyroid gland resection, in line with others [9] . In addition, intraoperatively, we also undertook a frozen section which confirmed that the excised specimen is parathyroid gland for both cases.…”
Section: Discussionmentioning
confidence: 54%
“…For age, although a study reported a mean age of 60 ± 13 years [1] , the age range is wide, where a 75-year-old female with ectopic APA has been described [8] , while another report depicted a 16-year-old adolescent girl who presented with severe PHPT manifestations due to APA [2] . Nevertheless, patients with an inherited condition causing APA present much younger, often in third decade [9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation